I'm Every Woman: Advancing the Intersectional Leadership of Black Women School Leaders as Anti-Racist Praxis. Issue 1 (January 2021) - Peters, April L.; Miles Nash, Angel
The rallying, clarion call to #SayHerName has prompted the United States to intentionally include the lives, voices, struggles, and contributions of Black women and countless others of her ilk who have suffered and strived in the midst of anti-Black racism. To advance a leadership framework that is rooted in the historicity of brilliance embodied in Black women's educational leadership, and their proclivity for resisting oppression, we expand on intersectional leadership. We develop this expansion along three dimensions of research centering Black women's leadership: the historical foundation of Black women's leadership in schools and communities, the epistemological basis of Black women's racialized and gendered experiences, and the ontological characterization of Black women's expertise in resisting anti-Black racism in educational settings. We conclude with a four tenet articulation detailing how intersectional leadership: (a) is explicitly anti-racist; (b) is explicitly anti-sexist; (c) explicitly acknowledges the multiplicative influences of marginalization centering race and gender, and across planes of identity; and (d) explicitly leverages authority to serve and protect historically underserved communities.